UJI EFEK ANTIDIABETES KOMBINASI EKSTRAK HERBA SAMBILOTO (Andrographis paniculata (Burm. F.) Nees.) DAN DAUN SIRSAK (Annona muricata L.) PADA TIKUS JANTAN YANG DIINDUKSI ALOKSAN - Maya Dwi Anggraini; Eka Wisnu Kusuma (As-Syifaa Jurnal Farmasi, 2019)
Diabetes mellitus(DM) is a disease characterized by an increase in blood sugar levels above normal. A lot of research about the medicine focusing on the use of plants that can be used in traditional medicines. This report is to know the combination of extract ethanol sambiloto herb and leaves the soursop to lower blood glucose levels on male rats wistar are induced alloxan. The research is an experimental research to pre and post test randomized controlled group. Treatment test consists of 8 groups: normal control, negative (alloxan), positive (glibenclamide 1,26 mg/kgBB), dose I SA 100 (sambiloto herb 20,5 mg/kgBB), dose II SR 100(leaves the soursop100 mg/kgBB), dose III SA:SR 25:75, dose IV SA:SR 50:50, dose V SA:SR 75:25. All groups (except normal) induced by alloxan 160 mg / KgBB. Then proceed with treatment test each drug group from day 0 to 14 in oral. Intake of blood glucose levels is done on days 0, 7 and 14. The results of the measurement of blood glucose levels followed by ANOVA. Combination sambiloto herb and leaves the soursop more effective to reduce blood glucose levels than single. Doses combination SA:SR 50:50 give the efffect of 28,38073%